2020
DOI: 10.18678/dtfd.628239
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hemogram Parameters in Febrile Seizures Types

Abstract: Aim: Febrile seizures (FS) are among the most common neurological emergencies during childhood and clinically classified into two types, being simple febrile seizures (SFS) and complicated febrile seizures (CFS). The differentiation between FS types is important, in that they are associated with different morbidity and mortality risks and it is based on the clinical characteristics of each seizure, however there is currently no laboratory test that can guide this differentiation. In this study, the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 20 publications
2
8
1
Order By: Relevance
“…Iron concentrations in blood could not be analyzed in the present study since the test was not routinely requested. One previous study comparing types of febrile seizure determined statistically significantly lower Hb, Htc and MCV values in patients with complex febrile seizure [19]. Similarly in the present study, we also observed significantly lower Hb, Htc and MCV values in the febrile convulsion group.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Iron concentrations in blood could not be analyzed in the present study since the test was not routinely requested. One previous study comparing types of febrile seizure determined statistically significantly lower Hb, Htc and MCV values in patients with complex febrile seizure [19]. Similarly in the present study, we also observed significantly lower Hb, Htc and MCV values in the febrile convulsion group.…”
Section: Resultssupporting
confidence: 90%
“…Türay et al observed significantly higher RDW in febrile seizure recurrence [21]. Örnek et al observed higher mean RDW in their complex febrile seizure group, but the difference was not statistically significant [19]. RDW was significantly higher in the simple febrile seizure group in the present study.…”
Section: Resultscontrasting
confidence: 67%
See 1 more Smart Citation
“…Of the 17 studies, ten studies reported NLR levels in children with FS and compared them with that of controls [ 8 , 11 , 13 , 15 18 , 20 , 22 , 24 ], and 11 studies compared the NLR levels in children with simple FS with those of children with complex FS [ 8 – 10 , 12 – 14 , 16 , 19 – 21 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The NLR, which can be calculated by absolute neutrophil count divided by absolute lymphocyte count, assessed based on a complete blood count (CBC) differential test, has been investigated in a number of previous studies involving cardiovascular diseases, malignancies [5,6], and some neurologic disorders [7]; however, the relevance between NLR and FS is still unclear. Although the controversy about the association between NLR and FS has raged unabated for about a decade [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], no systematic review has been reported. Therefore, our systematic review was conducted to determine whether NLR is associated with FS susceptibility and FS types in children.…”
Section: Introductionmentioning
confidence: 99%